Cho a+b+c bằng 0, chứng minh M bằng N bằng P với M: a(a+b)(a+c) N: (b+c)(b+a).b P: c(c+a)(c+b)

Question

Cho a+b+c bằng 0, chứng minh M bằng N bằng P với
M: a(a+b)(a+c)
N: (b+c)(b+a).b
P: c(c+a)(c+b)

in progress 0
Reagan 1 năm 2021-08-09T23:41:08+00:00 2 Answers 5 views 0

Answers ( )

    0
    2021-08-09T23:42:41+00:00

    Đáp án:

     

    Giải thích các bước giải:

     

    0
    2021-08-09T23:42:52+00:00

    Vì `a+b+c=0` nên : 

    $\left\{\begin{array}{l}
    a + b =-c \\
    a + c = -b\\
    b + c = -a
    \end{array}\right.$

    Khi đó ta có :

    `M = a . (a+b) . (a+c) = a . (-c) . (-b) = abc`
    `N = (b+c) . (b+a).b = -a . (-c) . b = abc`
    `P = c. (c+a).(c+b) = c . (-b) . (-a)  =abc`

    Suy ra `M=N=P`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )